Young Minds and Young Bodies: Supportive Teaching Strategies for Children with Mental Health Concerns. (2nd September 2020) - Watson, Dayna; Mowling, Claire M.
Abstract : Physical educators can expect to work with students experiencing a mental health concern. Mental health concerns are prevalent among children and adolescents in the United States. An estimated 13 to 20% of U.S. children meet the diagnostic criteria for an emotional or behavioral disorder. The purpose of this article is to provide physical educators with specific strategies to work effectively with students experiencing a range of mental health concerns. Described are key warning signs for identifying students that may be experiencing a mental health need, specific communication techniques, class environment considerations, and creative ways to use games to promote student mental health and wellness.